Research of ethics and deontological aspects in pharmacies - T. P. Zarichna; T. S. Brytanova; T. S. Raikova; T. A. Chornii (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of the study was to study the ethical and deontological aspects related to the professional activities of pharmacists.